Comparative Analyses Of The Human Soul In The Poetry Of Alisher Navai And William Shakespeare (Zien Journal of Social Sciences and Humanities, 2025)
The concept of the human soul has fascinated poets and philosophers for centuries. Among the greatest literary minds who explored the depths of the soul are Alisher Navai, a master of Chagatai literature, and William Shakespeare, the iconic English playwright and poet. Though they lived in different cultural contexts—Navai in the 15th-century Timurid Empire and Shakespeare in 16th–17th century England—their poetic works share a profound concern with the nature, struggles, and beauty of the human soul.